NONMEM Tutorial Part II: Estimation Methods and Advanced Examples - Robert J. Bauer (Wiley, 2019)
In this second tutorial on NONMEM, the examples of typical pharmacokinetic/pharmacodynamic modeling problems that occur in the pharmaceutical field will be presented, which the reader can use as a template for his or her own modeling endeavors. Each of the problems presented is challenging in some way, and the logic behind setting up each problem is discussed. Logical concepts of the problem itself as well as the technical aspect of how to set it up in NONMEM are described and demonstrated. The concepts behind the various estimation algorithms will first be described to allow the user a better understanding of how to use them.